2004
DOI: 10.5194/acp-4-1797-2004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tracer transport by a cumulus ensemble: lateral boundary conditions and large-scale ascent

Abstract: Abstract. The vertical transport of tracers by a cumulus ensemble at the TOGA-COARE site is modelled during a 7 day episode using 2-D and 3-D cloud-resolving setups of the Weather Research and Forecast (WRF) model. Lateral boundary conditions (LBC) for tracers, water vapour, and wind are specified and the horizontal advection of trace gases across the lateral domain boundaries is considered. Furthermore, the vertical advection of trace gases by the largescale motion (short: vertical large-scale advection of tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several model studies have shown that convection efficiently transports gases and particles into the free troposphere and reduces their concentrations below cloud with highest efficiency for gases that are not efficiently scavenged and removed during transport. Depending on transport time and cloud characteristics, it was found in theoretical model studies that 40–60% of inert, insoluble tracers were present within clouds, and that their concentrations were enhanced above cloud. ,,,− Because of the lack of appropriate observational data, results from the aforementioned sensitivity studies were not compared to observational data. Therefore, in the following mostly predicted trends from model studies are compared to those in observations; the few explicit model/observation comparison studies are highlighted.…”
Section: Comparisons Of Observations and Model Resultsmentioning
confidence: 99%
“…Several model studies have shown that convection efficiently transports gases and particles into the free troposphere and reduces their concentrations below cloud with highest efficiency for gases that are not efficiently scavenged and removed during transport. Depending on transport time and cloud characteristics, it was found in theoretical model studies that 40–60% of inert, insoluble tracers were present within clouds, and that their concentrations were enhanced above cloud. ,,,− Because of the lack of appropriate observational data, results from the aforementioned sensitivity studies were not compared to observational data. Therefore, in the following mostly predicted trends from model studies are compared to those in observations; the few explicit model/observation comparison studies are highlighted.…”
Section: Comparisons Of Observations and Model Resultsmentioning
confidence: 99%
“…A biomass burning plume as a cause of the upper-level trace gas enhancement can be excluded because acetonitrile, a distinct tracer for biomass burning, is not significantly enhanced (Lobert et al, 1990;Holzinger et al, 1999;Sanhueza et al, 2004).…”
Section: Measurement Datamentioning
confidence: 99%
“…4). Scala et al (1990) and Salzmann et al (2004) suggested rear inflow in mesoscale convective systems taking place in association with downward transport in the troposphere. This mechanism and cloud top entrainment (Boatman and Auer, 1983;Blyth et al, 1988) seem to be potential processes that could mix ozone-rich air in the anvil region from the layer above.…”
Section: Missing Ozone Sourcementioning
confidence: 99%
“…4). Scala et al (1990) and Salzmann et al (2004) suggested rear inflow in mesoscale convective systems taking place in association with downward transport in the troposphere. This mechanism and cloud top entrainment (Boatman and Auer, 1983;Blyth et al, 1988) seem to be potential processes that could mix ozone-rich air in the anvil region from the layer above.…”
Section: Missing Ozone Sourcementioning
confidence: 99%